Discrimination due to prejudice against people with visual impairment (Revista INTEREDU11, 2024)
This research addresses the issue of discrimination against people with visual impairment in the educational context, with emphasis on Mexican society where discrimination continues to exist. Discrimination has many facets and many of them are usually invisible because they are rooted in normalized practices, attitudes or policies, which is why it is a problem that can occur in any country, state or region.In the educational context, the rights of visually impaired people are often invisible2, and this is due to the lack of an educational program adapted for their accessibility. Likewise, acts of discrimination are committed by education professionals, who usually do not realize it. We are so used to the normality of people who can see, that we do not see and exclude this sector that also has the desire to improve and are usually in schools without infrastructure for their education. The purpose is to create awareness and empathy in society, in order to be part of the solution to eradicate discrimination against visually impaired people.
Keywords: visual impairment; discrimination; education; prejudice